Neonatal lupus erythematosus with persistent cutaneous telangiectases. - Menni, S.; Tribbia, G. (European Journal of Pediatric Dermatology, 1998)
Neonatal lupus erythematosus (NLE) is a rare disorder. It is characterized by cutaneous lesions and/or congenital heart block. Hematological abnormalities can be associated. The disorder is due to transplacental passage of anti-Ro/SSA and, less frequently, anti-La/SSB antibodies. A case on neonatal lupus erythematosus in a male child, who was born to a mother with Sjogren syndrome, is reported. The case was clinically characterized by persistent, punctiform telangiectases of the eyelids and, serologically, by increased level of autoantibodies to native 60-kd Ro/SSA, in spite of lacking heart involvement.